I Got a D in Salami - 1945-; Winkler, Henry; Oliver, Lin; Heyer, Carol; 1950- (New York, 2003)
Antics ensue after Hank throws his report card into a meat grinder.
Keywords: Report cards; Fiction; Schools; Fiction